Use of Intensive Care Unit in Women with Severe Maternal Morbidity and Maternal Death: Results from a National Multicenter Study - Soares, Fabiano M.; Guida, José Paulo; Pacagnella, Rodolfo Carvalho; Souza, João Paulo; Parpinelli, Mary Ângela; Haddad, Samira Maerrawi; Cecatti, José Guilherme (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To assess the use of the intensive care unit (ICU) and its effect on maternal mortality (MM) among women with severe maternal morbidity (SMM).Materials and Methods A secondary analysis of a cross-sectional study on surveillance of SMM in 27 Brazilian obstetric referral centers. The analysis focused on the association between ICU use and maternal death according to individual characteristics and disease severity. Two multivariate regressions considering use of the ICU, age, ethnicity, adequacy of care and the human development index were performed to identify the factors associated to maternal death and maternal near-miss.Results Out of 82,388 deliveries during the period, there were 9,555 (11.6%) women with SMM, and the MM ratio was of 170.4/100 thousand live births. In total, 8,135 (85.1%) patients were managed in facilities in which ICUs were available; however, only 2,059 (25.3%) had been admitted to the ICU. On the multivariate analysis, when the severity of the maternal disease was measured by the maternal severity score (MMS), the strength of the association between the use of the ICU and maternal death was greatly reduced, along with inadequate care and non-availability of the ICU at the facility. On the assessment of only the more critical cases (SMO, severe maternal outcome), the same pattern of association between ICU and MM was observed. In the models used, only inadequate care and MSS were significantly associated with MM.Conclusion The current study indicates that the main variables associated with maternal death are the severity and adequacy of the case management, which is more frequent in ICU admissions. The use of the ICU without the stratification of the patients by severity may not produce the expected benefits for part of the women.
Keywords: intensive care unit; severe maternal morbidity; maternal near-miss; complications of pregnancy